Vous êtes sur la page 1sur 8

E x x E x E

x E x / E

E = {1 , 2} x 2 3x + 2 = 0 R

E = {n N|(k N)(n = 2k)}

E = {3, 7, 9, 11}

 E = {1 , 3 , 5 , 7 , } E = {1 , 10 , 100 , 1000 , } ]0 , 1] f : R −→ R y f : R −→ R

A B

E ⊂ F
E ⊂ F
X x ∈ E x ∈ F
∀x,
x ∈ E =⇒ x ∈ F

R
A = R + ; B = {x ∈ R|x 2 0} ; C = {x ∈ R||x| > 1} ; D = ]−∞ ,
−1[ ; E = {x ∈ R|∀ > 0 , |x| < }

A ⊂ A
A ⊂ B B ⊂ A =⇒ A = B
A ⊂ B ⇐⇒ B ⊂ A

E = F ⇐⇒ (E F )

(F E) ⇐⇒ ∀x,

(x E ⇐⇒ x F )

1
1
A = n |n ∈ N ∗ B = n + 1 |n ∈ N
A = B

R (E); x 2 + 2x − 3 = 0

P(E) A ∈ P(E) ⇐⇒ A E

E = {x, y, z} P(E) = {∅, {x}, {y}, {z}, {x, y}, {x, z}, {y, z}, E}

A ⊂ B ⇐⇒ P(A) ⊂ P(B)

A B x x E

A B = {x E|(x E)

(x B)}

A B x x E

A B = {x E|(x E)

(x B)}

x B

x B

 A ∪ B x x ∈ E x ∈ B A ∪ B = {x ∈ E|(x ∈ E) (x ∈ B)} A ∩ B x x ∈ E x ∈ B A ∩ B = {x ∈ E|(x ∈ E) (x ∈ B)}

A B =

 E = R ; A = {−1 , 1} ; B = {x ∈ R||x| > 1} ; C = ]−1 , 1[ D = [−1 , 1]

A \ B x x ∈ A x
B
A \ B = {x ∈ E|(x ∈ A)
(x
∈ B)}
A B
A B = (A \ B) ∪ (B \ A)
E \ A A A c

A c = {x E|(x E)

(x

A)}

P(E)

A, B, C ∈ P(E)

A B = B A

A B = B A

(A B) C = A (B C)

(A B) C = A (B C)

A (B C) = (A B) (A C)

A (B C) = (A B) (A C)

A B = A B

B = A B

A

  A ∩ ∅ =

 

A ∪ ∅ = A

A B = ∅ ⇐⇒ A B

  A E = A

A E = E

 

A B = E ⇐⇒ B A

 A = B ⇐⇒ (A ⊂ B)
(B ⊂ A)
 
A ⊂ B ⇐⇒ B ⊂ A
(A ∪ B) ⊂ C ⇐⇒ (A ⊂ C)
(B ⊂ C)
 
A ⊂ (B ∩ C) ⇐⇒ (A ⊂ B)
(A ⊂ C)

 A A = ∅
 
 
 A E = A
 
A ∅ = A
A B = B A
 
 
 A (B C) = A (B) C
 
A ∩ (B C) = (A ∩ B) (A ∩ C)

f f x y f = (x E)(!y F )f (x) = y f : E −→ F

x −→

f(x)

f

f

f

x E f (x) x f

y F x y = f (x) x y f

f

f

 f : R −→ R x −→ x 2 f f f f
 f : E −→ F g : E −→ F f g (∀x ∈ E) f (x) = g(x) f = g
 f : E −→ F f Γ = {(x , f (x))/x ∈ E} = {(x , y)/x ∈ E, y ∈ F }

f : E −→ F f (A) = {y F |∃x A y = f (x)} = {f (x)|x E}

f : E −→ F f 1 (B) = {x E|f(x) B}

 f : E −→ F f |A : A −→ F x −→ f(x) f : E −→ F g : A −→ F g |A = f

  1   x , x = 0 R R g(x) = f : R ∗ −→ R R 0 1 x −→ x

 f : E −→ F ∀a, b ∈ E, f (a) = f (b) =⇒ a = b ∀a, b ∈ E, a = = b =⇒ f (a) f (b)

f : E −→

F

(y F )(x E),

y = f (x)

f : E −→

F

(y F )(!x E),

y = f (x)

f : E −→ F f 1 : F −→

E